On the Reliability of Accelerated Testing in AIGaAs/InGaAs/GaAs PHEMTs - K. F. Yarn; W. C. Chien; C. S. Wang (Active and Passive Electronic Components, 2002)
The study of different stress on device characteristics of AlGaAs/InGaAs/GaAs PHEMTs has been researched and developed in this report. Many catastrophic degradation mechanisms such as hot-electron, gate-drain breakdown, IDS, IG , VP and gate Schottky barrier effects are discussed in detail. In addition, the accelerated testing of the temperature-dependent effects on ID ,Gm and Schottky barrier are examined.